Analysis of genetic structure and diversity among lowland and midaltitude adapted maize inbred lines with AFLP markers - Menkir, A.; Gedil, Melaku A; Franco, J. (2010)
The extent of genetic diversity and genetic structure of 23 lowland and 23 mid-altitude adapted maize inbred lines that share a common source of resistance to the maize streak virus were surveyed using 18 amplified fragment length polymorphism (AFLP) primer pairs. Close to 86% of the 820 AFLP fragments were found in all the inbred lines adapted to the two zones. The remaining 14% of the fragments were present either in the lowland (SA) or mid-altitude (MA) inbred lines at frequencies varying from 4% to 56%. The genetic distance estimates for pairs of lines bred in each agro-ecological zone and those bred in the two agro-ecologies were broad. The number of combinations with genetic distance estimates exceeding 0.50 was highest in lowland × mid-altitude pairs, intermediate in lowland × lowland pairs and lowest in mid-altitude × mid-altitude pairs. The dendrogram constructed from genetic distance matrix using Ward's clustering method and principal component analysis separated the lines into groups along their areas of adaptation. The frequency based fixation index calculated using a Bayesian approach under the hypothesis of high self fertilization and analysis of molecular variance also found significant differentiation between the lowland and mid-altitude adapted maize inbred lines. These results can form the basis for selecting diverse parental lines from one zone as sources of novel alleles for introgression into another zone. This may also facilitate selection of diverse parental lines with complementary traits from one zone to make crosses with lines in another zone to develop new generation of inbred lines.